Impact of On-line Physical Activity Sessions on the Well-Being of Older People: The Value of the University Extension - Solano-Mora, Luis (2023)
The purpose of this study was to carry out an exploratory analysis of the value of on-line physical activity sessions proposed from the university extension on the well-being of a group of older adults. Methodology: A protocol for physical activities focused on virtual sessions for older adults was developed. 12 sessions were applied and at the end, both the participants and the instructors were sent a digital questionnaire to provide their impressions of what they experienced in this period. Results: The participants showed in general, a better physical state and a positive response when doing physical activities on-line, and instructors expressed their satisfaction with the on-line modality. Conclusion: The participants indicated that the on-line sessions felt very good and helped them improve their physical condition, so the university should consider this strategy in its actions to be developed from the university extension.